Calpain inhibitor calpeptin suppresses pancreatic cancer by disrupting cancer–stromal interactions in a mouse xenograft model. Issue 10 (24th September 2016) - Yoshida, Masaki; Miyasaka, Yoshihiro; Ohuchida, Kenoki; Okumura, Takashi; Zheng, Biao; Torata, Nobuhiro; Fujita, Hayato; Nabae, Toshinaga; Manabe, Tatsuya; Shimamoto, Masaya; Ohtsuka, Takao; Mizumoto, Kazuhiro; et al.
Abstract : Desmoplasia contributes to the aggressive behavior of pancreatic cancer. However, recent clinical trials testing several antifibrotic agents on pancreatic cancer have not shown clear efficacy. Therefore, further investigation of desmoplasia‐targeting antifibrotic agents by another mechanism is needed. Calpeptin, an inhibitor of calpains, suppressed fibroblast function and inhibited fibrosis. In this study, we investigated the anticancer effects of calpeptin on pancreatic cancer. We investigated whether calpeptin inhibited tumor progression using a mouse xenograft model. We used quantitative RT‐PCR to evaluate the expression of calpain‐1 and calpain‐2 mRNA in pancreatic cancer cells (PCCs) and pancreatic stellate cells (PSCs). We also undertook functional assays, including proliferation, migration, and invasion, to evaluate the inhibitory effects of calpeptin on PCCs and PSCs. Quantitative RT‐PCR indicated that PCCs and PSCs expressed calpain‐2 mRNA. Calpeptin reduced tumor volume ( P = 0.0473) and tumor weight ( P = 0.0471) and inhibited the tumor desmoplastic reaction ( P < 0.001) in xenograft tumors in nude mice. Calpeptin also inhibited the biologic functions of PCCs and PSCs including proliferation ( P = 0.017), migration ( P = 0.027), and invasion ( P = 0.035) in vitro . Furthermore, calpeptin reduced the migration of PCCs and PSCs by disrupting the cancer–stromal interaction ( P = 0.0002). Our findings indicate that calpeptin is a promising antitumor agent for pancreatic cancer, due not only to its suppressive effect on PCCs and PSCs but also its disruption of the cancer–stromal interaction. Abstract : Calpeptin, a calpain inhibitor, reduced the volume of xenograft tumors containing pancreatic cancer cells (PCCs) and pancreatic stellate cells (PSCs). Calpeptin suppressed proliferation, migration, and invasion of PCCs and PSCs. Furthermore, calpeptin reduced the migration of PCCs and PSCs by disrupting the cancer‐stromal interaction.